2018
DOI: 10.1016/j.toxrep.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A (BPA) the mighty and the mutagenic

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
114
0
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(125 citation statements)
references
References 92 publications
(102 reference statements)
1
114
0
10
Order By: Relevance
“…In turn, changes in neurons immunoreactive to various substances suggest multidirectional effects of BPA on the ENS. The fluctuations in the immunoreactivity of the enteric neurons noted in the present study may result from the genotoxic effects of BPA and disturbances in protein synthesis on various levels, as well as disorders in the intraneuronal transport of the active factors studied. The changes are probably connected with pro‐inflammatory neurotoxic and/or relaxant impact of BPA, but it should be noted that the exact mechanisms of the observed fluctuations remain unclear and require further investigation.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…In turn, changes in neurons immunoreactive to various substances suggest multidirectional effects of BPA on the ENS. The fluctuations in the immunoreactivity of the enteric neurons noted in the present study may result from the genotoxic effects of BPA and disturbances in protein synthesis on various levels, as well as disorders in the intraneuronal transport of the active factors studied. The changes are probably connected with pro‐inflammatory neurotoxic and/or relaxant impact of BPA, but it should be noted that the exact mechanisms of the observed fluctuations remain unclear and require further investigation.…”
Section: Discussionmentioning
confidence: 60%
“…In turn, changes in neurons immunoreactive to various substances suggest multidirectional effects of BPA on the ENS. The fluctuations in the immunoreactivity of the enteric neurons noted in the present study may result from the genotoxic effects of BPA 6,50 and disturbances in protein synthesis on various levels, as well as disorders in the intraneuronal transport of the active factors studied.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Thereby, it must be highlighted that BPA is one of the most widely used synthetic compounds worldwide and can adversely impact human health, especially infants (Jalal et al, 2018). BPA is usually applied in production of specific polycarbonate plastic and epoxy resins coatings for cans.…”
Section: Food-package Interactionmentioning
confidence: 99%
“…However, BPA was commonly found in human blood with concentrations between 0.1-100 nM [28] and its conjugated form was found in urines samples with average values between 2-650 nM [29]. An interesting study found a statistically higher BPA concentration in urine samples in females than in males and higher BPA in children than in adults [30], but the reasons are not clear yet. A randomized clinical trial showed that consuming canned beverage augmented urinary BPA concentration and increased blood pressure [31,32].…”
mentioning
confidence: 99%